2013
DOI: 10.5959/eimj.v5i1.16
|View full text |Cite
|
Sign up to set email alerts
|

Social Factors Influencing Career Choice in a Medical School in the United Arab Emirates

Abstract: Objective: The goal of this research was to identify familial and nonfamilial social factors influencing post-secondary students' choices of career in medicine. Method: The comparative study was conducted in Ajman, among medical students in the beginning three years, and nonmedical students at the same educational level. After obtaining verbal consent, the participants completed a pilot tested, self-administered questionnaire which included socio-demographic variables and social factors related to career choic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 7 publications
2
6
0
1
Order By: Relevance
“…This is an insufficiently explored area and deserves consideration as part of training efforts of future generations of health professionals. The role of family factors in the decision to choose a medical career, previously reported [ 31 , 40 , 42 ], has also been found in our study, reflecting the positive role that family models play in shaping young people’s career choice decisions.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This is an insufficiently explored area and deserves consideration as part of training efforts of future generations of health professionals. The role of family factors in the decision to choose a medical career, previously reported [ 31 , 40 , 42 ], has also been found in our study, reflecting the positive role that family models play in shaping young people’s career choice decisions.…”
Section: Discussionsupporting
confidence: 87%
“…Our medical students believed that by becoming doctors they can guarantee their later professional, economic and social status, which is at odds with the generalized perception that medicine does not guarantee anymore a profitable future [ 31 , 42 , 43 ], unless doctors resort to multiple practice appointments [ 42 , 43 ]. This may be due to the fact that students have not experienced yet the actual constraints imposed by the labour market, which privileges professions related to productive and technological activities [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, it was found that urban students may find it harder to adjust and may not work longer than the length of their bursaries. 41 Reasons for choosing an optometry career in South Africa are similar in Saudi Arabia 42 and Ghana 40 -a desire to help others and job availability were the most commonly expressed motives. In interviews, it emerged that exposure to clinical role models (visiting optometrists with parents, volunteering with an optometry student, for example) had some influence on their career choice -corresponding with studies of young doctors 43 and clinical nurses.…”
Section: Recruitmentmentioning
confidence: 99%
“…Research have shown that families, especially parents, play an important role in identifying their children's talents and directing their educational journey. [ 1 2 ] Family factor is the first environment for an individual to grow and develop in a personal way. Most medical students believe parents have a heavy impact on career choices, while others make career choices with their parents.…”
Section: Introductionmentioning
confidence: 99%